Implementasi Otomasi Pju Berbasis Iot Menggunakan Energi Terbarukan di Jlumpang Nganjuk - R. Akbar Nur Apriyanto; Echsony, Mohammad Erik; R. Gaguk Pratama Yudha; Adiratna Ciptaningrum; Hanum Arrosida; Givan Sang Pradana (LPPM UMRI, 2026)
This Community Service Program aimed to implement an Internet of Things (IoT)-based Public Street Lighting (PSL) automation system powered by renewable energy in Jlumpang RT 04 RW 01, Nganjuk Regency. The program adopted a Participatory Action Research approach consisting of field surveys, community socialization, system design, installation, training, and evaluation. The implemented system integrated a solar photovoltaic panel, battery, solar charge controller, Light Dependent Resistor (LDR), ESP32 microcontroller, relay, and LED street lamp. Technical evaluation demonstrated that all components operated according to their specifications, with solar panel output voltage of 20.48–21.23 V, charging current of 4.32–4.68 A, lighting intensity of 32.4–36.7 lux in compliance with SNI 7391:2008, and stable IoT communication performance. Training evaluation indicated a significant improvement in participants' knowledge from 43.75% to 90.0%, while the overall participant satisfaction reached 92.4%, categorized as excellent. The implemented system successfully improved street lighting quality, energy efficiency, and community capacity in operating and maintaining IoT-based technology. This program demonstrates the potential of smart renewable-energy street lighting as a sustainable solution for community infrastructure development.